KEBERHASILAN KOMPETENSI LITERASI DIGITAL SEBAGAI TOLOK UKUR SOFT SKILLS MAHASISWA LULUSAN KEARSIPAN - Maharani, Dewi; Wijayanti, Wijayanti (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
This article was written to deliver the idea of the need for digital literacy competencies for archival graduate students in an era of disruption to meet the needs of users and professional development so that in the end the success of digital literacy becomes a new benchmark for soft skills competencies for archiving program graduates. This research is a descriptive qualitative study using the FGD method for collecting data from informants, namely users and graduates of the archiving program itself. The results show that graduates of archives have not been able to meet the needs of soft skill competencies according to user demands, especially regarding the use of digital technology in supporting the implementation of tasks and jobs. It is suggested that college can facilitate the efforts to increase digital literacy competence through learning methods, in addition to students also trying to improve their experience in the use of digital technology.